Study of Ammonium Sulfide Surface Treatment for Ultrathin Cu(In, Ga)Se2 with Different Cu/(Ga + In) Ratios. Issue 19 (26th August 2020) - Buldu, Dilara Gokcen; de Wild, Jessica; Kohl, Thierry; Brammertz, Guy; Birant, Gizem; Meuris, Marc; Poortmans, Jef; Vermang, Bart
Abstract : In ultrathin Cu(In, Ga)Se2 (CIGS) film solar cells, the CdS/CIGS interface may become one of the limiting factors for efficiency. The first step toward reducing the impact of this problem could be a surface treatment process to improve the quality of the front interface. The purpose of this study is to have a better understanding of the effect of wet chemical surface treatment, using ammonium sulfide ((NH4 )2 S), on CIGS thin film layers with different Cu/(Ga + In) (CGI) ratios. Herein, photoluminescence (PL) and time‐resolved PL (TRPL) studies are conducted on bare CIGS, ammonium sulfide–treated CIGS thin films, and samples with CdS. In bare CIGS, CGI ratio–dependent changes in PL are observed on both a low‐energy (defect related transition) and a high‐energy peak (band‐to‐band transition). After the surface treatment, the PL maximum increases by factors ranging from 4 to 11 depending on the CGI ratio, accompanied by a slower decay. Trends with similar improvement as in the PL study are observed in the performance of the solar cells. It is shown that the impact of the surface treatment is beneficial independently of the CGI ratio of the absorber layers. In all cases, the treatment is shown to improve the efficiency. Abstract : Herein, it is shown that ammonium sulfide surface treatment plays a key role in improving the buffer layer/Cu(In, Ga)Se2 (CIGS) interface. The exact impact of the surface treatment could be different depending on the Cu/(Ga + In) ratio. However, independent of this ratio, ammonium sulfide surface treatment has a net positive effect on the performance of all studied samples.